Antifungal Activity and Identification of Active Compounds From Wood Tristaniopsis whiteana (Griff) Against Wood Rot Fungus - Jemi, Renhart; Syafii, Wasrin; Febrianto, Fauzi; Hanafi, Muhammad (Wood Research Journal, 2024)
The aim of the study was to analyze the content of pelawan wood extractive substances (Tristaniopsis whiteana (Griff)) and to test it with the fungi Schizophyllum commune Fr and Pleurotus ostreatus. Pelawan heartwood powder was macerated with methanol. Then fractionated in stages with n-hexane, chloroform, ethyl acetate, and butanol. The resulting extract was then tested with S. commune and P. ostreatus fungi. The most active fraction was isolated using column chromatography with a gradient system, the eluent was methanol:chloroform. Sub-fractions were then tested for fungi to determine the most active sub-fractions, and the most active sub-fractions were then analyzed by 1H NMR. The results showed that the extractive content of pelawan wood was most soluble in chloroform. All extract fractions contain potential as anti-fungal. .The chloroform fraction was very active compared to the other fractions. Isolation of the chloroform fraction by column chromatography obtained 8 sub-fractions. All of these sub-fractions were able to inhibit the growth of S.commune and P.ostreatus with IC(50) = 54.55 - 64.69 mg/L and IC(50) = 54.17 - 64.44 mg/L respectively. PL.3 sub-fraction was the most active among the 8 sub-fractions. The results of 1H NMR analysis on the PL.3 subfraction were shown to be Heptanoic Acid compounds.